NIKAH LINTAS AGAMA PERSPEKTIF HUKUM ISLAM - Syam, Aydi (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
Focus of this paper is to study the legality of Islamic law on interfaith marriage . Basing on some proposition naqliy understood that there are two laws that are contradictory, that is: absolutely forbidden marriage and marriage is permitted / allowed conditionally. This conclusion is based on the QS. al-Baqarah (2) : 221 ; QS. al-Mumtahanah (60) : 10 ; and QS. al-Maâidah (5) : 5. While understanding the argument of the methodology used is the type of pattern bayÄniy mauÄÅ«âiy, tahlÄ«liy, and muqÄran. While the multidisciplinary approach is more focused on the study of semiotics, historical and culture analysis.